Towards Vulnerability Prevention Model for Web Browser using Interceptor Approach - Nayeem, Khan; Johari, Abdullah; Adnan, Shahid Khan (2015)
Cross Site Scripting (XSS) is popular security vulnerability in modern web applications. XSS attacks are malicious scripts which are embedded by attackers into the source code of web page to be executed at client side by browsers. Researchers have proposed many techniques for detection and prevention of XSS, but eliminating XSS still remains a challenge. In this paper the authors propose a web security model for XSS vulnerability prevention for web browsers using interceptor approach. Several client and server side solution have been proposed but they degrade the browsing performance and increases configuration overheads. The proposed model is an effective solution with minimal performance overheads using both Client and Server side location in detection and prevention of XSS.